2011
DOI: 10.1097/aog.0b013e318207854f
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted, Laparoscopic, and Abdominal Myomectomy: A Comparison of Surgical Outcomes

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
128
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(147 citation statements)
references
References 22 publications
4
128
5
2
Order By: Relevance
“…18,20 Technical advantages of robotic-assisted laparoscopic surgery may help overcome these challenges and perhaps improve the adoption of the laparoscopic technique. 8,11 These advantages include 3-dimensional visualization, instrument articulation, improved dexterity, and the elimination of tremor and counterintuitive movements. 21,22 Specifically, these advantages offer the community-based gynecologist greater facility with which to suture and surgically dissect laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 Technical advantages of robotic-assisted laparoscopic surgery may help overcome these challenges and perhaps improve the adoption of the laparoscopic technique. 8,11 These advantages include 3-dimensional visualization, instrument articulation, improved dexterity, and the elimination of tremor and counterintuitive movements. 21,22 Specifically, these advantages offer the community-based gynecologist greater facility with which to suture and surgically dissect laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have confirmed the longer operating time and shorter length of stay [51,52] [55]. There are few published studies assessing the role of robot-assisted surgery in fertility.…”
Section: Fertility: Myomectomymentioning
confidence: 89%
“…The cost of surgery can be minimized when performed by an experienced surgeon with decreased operative time and may be further offset by the decreased length of inpatient stay compared with laparotomy. 39 Initial hospital charges have been found to be higher with lower physician reimbursement for robot-assisted surgery. 17 However, as the costs secondary to depreciation of the robot decrease in combination with lower complication rates, length of stay, and nursing costs, robot-assisted technology may become the more optimal financial option.…”
Section: Discussionmentioning
confidence: 99%
“…39 Compared to laparotomy, patients undergoing RALM have been shown to have a significantly less blood loss, a smaller change in postoperative hematocrit, and a shorter length of stay. 17 Furthermore, RALM may avoid complications associated with myomectomy performed by laparotomy, including postoperative hemorrhage, ileus, bowel obstruction, cystotomy, and pelvic abscess formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation